The dialogue between the intellectual property provisions in preferential trade agreements and the Brazilian legal framework - Mesquita, Alebe Linhares (2018)
The present work promotes a dialogue between the intellectual property provisions adopted in Preferential Trade Agreements (PTAs) and the Brazilian legal framework. In recent years, PTAs have become a major source of international intellectual property regulation. This happens in parallel to the multilateral trading system and rules established under the auspices of the World Trade Organization (WTO). The new intellectual property provisions established under PTAs advance significantly the rules established under the WTO Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement). In this scenario, Brazil is apart from the international economic trend of adopting intellectual property provisions in PTAs. Due to its inaction, the country cannot influence the direction in which the international intellectual property regulation is heading. This issue is analyzed in the light of the balance between private and public interests that the protection of intellectual property rights imposes. The general objective of the present work is to investigate how and to what extent the intellectual property rules established under PTAs differs from the Brazilian intellectual property regime. The specific objectives are to assess which are the legal issues and the possible effects that pervade the adoption higher standards of intellectual property protection in PTAs; to map and analyze the norms on patent and test data protection adopted in PTAs and to compare them with the TRIPS Agreement and the Brazilian intellectual property regime; and to investigate how intellectual property rules are diffused across international, regional and national levels. The methodology adopted in this research is characterized as bibliographic, descriptive and exploratory. The importance of this research resides in understanding the cross cutting trends in the establishment of new intellectual property rules. This work concludes that the intellectual property rules on patent and test data protection accorded under PTAs do not radically differ from the Brazilian intellectual property regime. Brazil already has several provisions in its national legislation that even exceed the level of patent and test data protection required under these PTAs and the TRIPS Agreement. On the one hand, the Brazilian intellectual property regime differs from the following TRIPS-Plus provisions on: patentability of methods of treatment, plants and animals; limitation of the grounds for compulsory license; restriction of the grounds for patent revocation; adjustment to compensate the curtailment of the patent term due to the marketing approval procedures; patent-linkage; and test data exclusivity of pharmaceutical products for human use submitted to marketing approval. On the other hand, the Brazilian intellectual property regime aligns with the following TRIPS-Plus provision: prohibition of parallel importation of patented products; patentability of \"new uses\" of known compounds; adjustment in the patent term of protection to compensate unreasonable delays in the granting process; disclosure of the origin of the national genetic resource and associated traditional knowledge in patent applications; test data exclusivity of pharmaceutical products for veterinary use and plant protection products.